The impact of mothers working shift patterns with emotional behavior of preschool age children at RSUD dr Saiful Anwar Malang - S. Diana Kushandayani; Risna Yekti Mumpuni; Agnis Sabbat Kristiana (University of Muhammadiyah Malang, 2022)
Introduction: Children’s social-emotional development includes the development of emotions, personality, and interpersonal relationships. Preschoolers are in an active period in personality formation and social development. Children's social-emotional development is influenced by several factors: interaction in the family, especially with the mother. Mother is a central figure who plays an essential role in meeting the welfare and needs of family members. The child's interaction with the mother will be disturbed when the mother is working. Objectives: This study aims to determine the relationship between working mothers and shift patterns in the emotional behavior of preschoolers. Methods: The research design used is correlation analytic with a cross-sectional approach. Irna IV Hospital dr. Saiful Anwar Malang, who has preschool-age children, is the population in this study. The sampling method is purposive sampling. The instrument used is the impact of the mother's work shift pattern and emotional behavior problems. Spearman's Rank test determines the relationship between the two variables. Results: Of the 54 employees recruited in this study. The analysis results showed a significant relationship p = 0.000 <0.05 between the two variables, with a strong correlation value (r = 0.67). Conclusions: there is a significant relationship between working mothers and shift patterns in the quality of interaction with children. Disturbance of mother-child interaction affects children's emotional behavior, especially in preschoolers.